DIFFICULTIES FOUND BY ELDERLY CAREGIVERS WITH ALZHEIMER: DIFFICULTIES FOUND BY ELDERLY CAREGIVERS WITH ALZHEIMER - Souza, Ellen Caliane de; Silva, Talina Carla da; Silva, Macerlane de Lira; Nascimento, Ingridy Michely Gadelha do; Alencar, Matheus Tavares; Feitosa, Ankilma do Nascimento Andrade (Brazilian Journal of Production Engineering, 2020)
Introduction: Aging is a common phenomenon throughout the world, which causes changes in health status that commonly require care. Alzheimer’s is a very common pathology in the elderly population. Objective: To identify the adversities that caregivers of elderly people with Alzheimer’s face. Methodology: An Integrative Literature Review, which had the following guiding question: What are the biggest obstacles that caregivers of elderly people with Alzheimer’s face? The search took place from September to October 2020, in the database: MEDLINE and in the virtual library: Scielo, using the descriptors: "Elderly", "Caregivers" and "Alzheimer". The study included: articles published in the years 2015 to 2020, available in full, free of charge, in Portuguese, and which were in accordance with the objective proposed by the research, being excluded: editorials, letters to the editor, review studies, thesis, dissertation duplicate articles and studies that did not correspond to the relevant study theme, the sample being composed of 13 articles. Results and Discussion: The most frequent difficulties encountered are comfort and cleanliness, the need for constant actions and the absence of information about the pathology in question, as well as health problems of the caregiver; full dedication to care and impaired social life; and agree with the circumstances of submission of the elderly, exchange of roles. Conclusion: the study showed daily challenges in the caregivers’ daily life and revealed the need to address the health problems that arise as a result of the accumulation of activities developed by these individuals.